Heterospecific and conspecific associations of trees in lowland tropical forest of New Guinea - Agustinus Murdjoko; MARTHEN MATHIAS JITMAU; DONY ARISTONE DJITMAU; RIMA HERLINA SETIAWATI SIBURIAN; ANTONI UNGIRWALU; ALFREDO OTTOW WANMA; ZULFIKAR MARDIYADI; ALEXANDER RUMATORA; WOLFRAM YAHYA MOFU; ANTON SILAS SINERI; SEPUS MARTEN FATEM; DESCARLO WORABAI; NUNANG LAMAEK MAY; MAX JONDUDAGO TOKEDE; HERMAN WARMETAN; CHARLY BRAVO WANGGAI; JIMMY FRANS WANMA; ELIESER VIKTOR SIRAMI; JOHANA BETY PAEMBONAN; ERNI UNENOR; RELAWAN KUSWANDI; KRISMA LEKITOO; LISNA KHAYATI; NITHANEL MIKAEL HENDRIK BENU; JUNUS TAMBING; ANDI SASTRA BENNY SARAGIH (Society for Indonesian Biodiversity, 2020)
Abstract. Murdjoko A, Jitmau MM, Djitmau DA, Siburian RHS, Ungirwalu A, Wanma AO, Mardiyadi Z, Rumatora A, Mofu WY, Sineri AS, Fatem SM, Worabai D, May NL, Tokede MJ, Warmetan H, Wanggai CB, Wanma JF, Sirami EV, Paembonan JB, Unenor E, Kuswandi R, Lekitoo K, Khayati L, Benu NMH, Tambing J, Saragih ASB. 2020. Heterospecific and conspecific associations of trees in lowland tropical forest of New Guinea. Biodiversitas 21: 4405-4418. The vegetation in the tropical rainforest of New Guinea consists of a large number of species that interact with each other within and among species. While several studies have attempted to reveal the diversity of flora of New Guinea, little is known about plant communities that develop associations. This study aimed to investigate the associations of tree species in lowland tropical forest in New Guinea. The associations depicted in this study were in the form of conspecific associations (among small and large individuals within same species) and heterospecific (among individuals of different species and divided into under and upper story). We established 48 rectangular plots created in Murkim and Teiraplu as part of Pegunungan Bintang Regency, Papua Province. Canonical correspondence analysis (CCA) was used to analyze heterospecific and conspecific associations. The results showed that the understory and upper story vegetation had different patterns of heterospecific association. The understory configured three heterospecific associations, consisting of 5, 13, and 90 species, while the upper story formed four heterospecific associations with 4, 8, 11, and 63 species. The analysis of conspecific associations showed of 149 tree species recorded in the study sites, only 66 species that had both small and large individuals, displaying the pattern of conspecific association. Among them, 41 species had positive associations while 25 species had negative associations. Our findings enrich the knowledge in theoretical ecology of tropical forests, especially in New Guinea.